2019
DOI: 10.1038/s41598-019-42934-z
|View full text |Cite
|
Sign up to set email alerts
|

Early Synaptic Alterations and Selective Adhesion Signaling in Hippocampal Dendritic Zones Following Organophosphate Exposure

Abstract: Organophosphates account for many of the world’s deadliest poisons. They inhibit acetylcholinesterase causing cholinergic crises that lead to seizures and death, while survivors commonly experience long-term neurological problems. Here, we treated brain explants with the organophosphate compound paraoxon and uncovered a unique mechanism of neurotoxicity. Paraoxon-exposed hippocampal slice cultures exhibited progressive declines in synaptophysin, synapsin II, and PSD-95, whereas reduction in GluR1 was slower an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 80 publications
0
13
0
Order By: Relevance
“…All brain regions assessed demonstrated significant astrocytic reactivity with high dose permethrin, but of note is the marked immunoreactivity recorded in the prefrontal and cerebellar cortices. Deterioration in cognitive functions is a hallmark of synaptic pathology seen in several neurologic disorders, such as Alzheimer’s disease, amyotrophic lateral sclerosis and Parkinson’s disease [ 58 60 ], and oxidative stress and lipid peroxidation have been identified as part of a common pathophysiology of these neurodegenerative conditions [ 11 , 59 ]. The findings above correlated well with the depressed endogenous oxidative status that followed permethrin toxicity, and the oxidative stress has been suggested to be part of the pathophysiology of neurologic conditions associated with neurotoxicity [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…All brain regions assessed demonstrated significant astrocytic reactivity with high dose permethrin, but of note is the marked immunoreactivity recorded in the prefrontal and cerebellar cortices. Deterioration in cognitive functions is a hallmark of synaptic pathology seen in several neurologic disorders, such as Alzheimer’s disease, amyotrophic lateral sclerosis and Parkinson’s disease [ 58 60 ], and oxidative stress and lipid peroxidation have been identified as part of a common pathophysiology of these neurodegenerative conditions [ 11 , 59 ]. The findings above correlated well with the depressed endogenous oxidative status that followed permethrin toxicity, and the oxidative stress has been suggested to be part of the pathophysiology of neurologic conditions associated with neurotoxicity [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Protein contents of homogenized samples were determined with a colorimetric protein assay and a bovine serum albumin (BSA) standard curve, and equal protein amounts of compared samples were denatured for 5 min at 100 °C, separated by SDS-PAGE, and transferred to nitrocellulose membranes for immunolabeling procedures as previously described [49,87,88]. Antibodies utilized were developed against cathepsin B (1:200; Millipore; Danvers, Massachusetts, USA), β-actin (1:1000; Sigma-Aldrich), amino acids 1–16 of human Aβ (6E10, 1:500; Covance; Princeton, New Jersey, USA), human sAPPα (2B3, 1:100, IBL International; Morrisville, North Carolina, USA), AMPA receptor subunit GluR1 [89] (1:300; or 1:1000 when supplied from Millipore), NCAM-180 (1:300; Abcam), human α-synuclein (1:200; Abcam), and SRPX2 (1:300; Proteintech Group, Inc., Rosemont, Illinois, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Fixed tissue was cryoprotected and serially sectioned at a thickness of 10–20 μm. The tissue sections were immunolabeled using 6E10 antibody (Covance), anti-calbindin D28k (Sigma-Aldrich), anti-GluR1 (from Millipore or developed as described [88]), anti-LAMP1 (BD Pharmingen; San Jose, California, USA), anti-cathepsin B (Millipore), anti-synaptophysin (Millipore), and antibodies that selectively label Aβ38 and Aβ42 (Covance). Immunofluorescence analyses used appropriate Invitrogen secondary antibodies (Thermo Fisher Scientific; Waltham, Massachusetts, USA), and images were captured with a Zeiss fluorescence microscope system (Carl Zeiss, Inc.; Thornwood, New York, USA) and with a Nikon C2 point-scanning confocal microscope with NIS-Elements AR software (Nikon Instruments; Melville, New York, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Integrins affect neurite outgrowth in adult healthy brains and pathological conditions [ 45 47 ]. Farizatto et al found that the overexpression of integrin β 1 regulated synapse maintenance and plasticity [ 48 ]. However, some research showed that the lower level of integrin β 1 reduced dendrite growth, suggesting that integrin β 1/FAK signaling pathway was involved in neurite outgrowth, which contributed to the differentiation of neuronal cells and determined the outcome of patients [ 31 , 49 ].…”
Section: Discussionmentioning
confidence: 99%